Side-effects and tolerability of combination blood pressure lowering according to blood pressure levels – an analysis of the PROGRESS and ADVANCE trials - Atkins, A; Hirakawa, Y; Salam, A; Woodward, M; Cooper, M; Hamet, P; Harrap, S; Lees, K; Lisheng, L; Mancia, G; Marre, M; Perkovic, V; et al. (Lippincott, Williams & Wilkins, 2017)
Objective: To measure the placebo-controlled effects of combination therapy on hypotension, treatment discontinuation and major renal outcomes, according to baseline blood pressure. Methods: We conducted an analysis of the ADVANCE and PROGRESS trials, including 14,684 participants allocated combination therapy or placebo. The mean age was 65 years, 61% were male and 64% were receiving background blood pressure lowering therapy. Participants were stratified into five subgroups by baseline systolic blood pressure (SBP) <120mmHg, 120-129mmHg, 130-139mmHg, 140-159mmHg, and ≥160mmHg. Discontinuation of study treatment during the active run-in phase and post-randomization follow-up was assessed for hypotension/dizziness and other causes. Major renal outcomes (sustained doubling in creatinine or renal death) were also assessed. Results: Discontinuation during the 4-6-week active run-in phase due to hypotension/dizziness ranged from 3.6% in those with SBP <120mmHg to 1.3% in those with SBP≥160mmHg. Median follow-up in the randomized phase was 5.6 years, and discontinuation for hypotension was higher with combination therapy compared to placebo in the <120mmHg group (4.7% vs. 1.2%). However, for each subgroup with baseline SBP 120-129, 130-139 and 140-159mmHg the absolute excess of discontinuation due to hypotension with combination therapy was 0.7%. Total discontinuations were only increased in the <120mmHg group (18.4% vs. 12.5%) and the 120-129mmHg subgroup (17.6% vs. 14.2%). There were no clear differences across the SBP subgroups for the combined renal outcome (overall, 0.8% vs. 0.6%). Conclusion: Compared to those with baseline SBP140-159mmHg, side-effects of dual combination blood-pressure lowering are essentially the same for people with SBP130-139mmHg and only modestly increased among patients with SBP120-129mmHg. During long-term therapy, side-effects sufficient to stop treatment that are treatment related (i.e. occur in excess of rates seen with placebo) occur at <0.5%/year in patients with baseline SBP120-139mmHg. These results have important implications in assessing the likely balance of benefits and side-effects of blood-pressure lowering with combination therapy among those with SBP120-139mmHg.